Wuthering heights - Brontë, Emily, 1818-1848 (Rupa, 2004)
It is a story of exceptional emotional and imaginative force. Heathcliff, a stray of unknown parentage, is picked up by Mr. Earnshaw's death, his son hindley bullies and humiliates heathcliff, who has found a soulmate in catherine who shares with him his ferocious and passionate nature. Catherine reluctance to marry him forces heathcliff to leave the house and to returns three year later, having mysteriously become quite rich. Heathcliff, however is set up on destroy the family. this he does, first by marring Linto's sister and cruelly ill-treating her, then by betrying his ferocious passion for Catherine, who dies in the process giving birth to a child, Cathy. he tries to force a union between his son Linton and Cathy's father, Edgar, vainly tries to prevent . After edgards death, Heatchiff forces the marriage, but young Kinton soon dies. cathy is now an unwilling prisoner at the heights, but she befriends hareton, Hindly's son, whom she tries to educate Heathcliff's passion for revenge has, however, burnt itself out, and all that he wants now is death, which will unite him with his first love, Catherine